1996
DOI: 10.1128/jb.178.20.6056-6058.1996
|View full text |Cite
|
Sign up to set email alerts
|

Active efflux of toluene in a solvent-resistant bacterium

Abstract: We investigated the mechanisms behind the organic-solvent resistance of the solvent-tolerant strain Pseudomonas putida S12. By use of 14 C-labeled toluene, we obtained evidence that an energy-dependent export system may be responsible for this resistance to toluene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 15 publications
1
102
0
Order By: Relevance
“…This finding may reflect greater expression of acrAB in Mar mutants or a combination of acrAB overexpression and the other changes occurring in a Mar mutant. It is interesting that efflux was associated with toluene resistance in Pseudomonas putida, although the genes were not identified (29).…”
Section: Discussionmentioning
confidence: 99%
“…This finding may reflect greater expression of acrAB in Mar mutants or a combination of acrAB overexpression and the other changes occurring in a Mar mutant. It is interesting that efflux was associated with toluene resistance in Pseudomonas putida, although the genes were not identified (29).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the degree of toxicity of an organic solvent corresponds to its log P ow value, which is the logarithm of the partition coefficient of the organic solvent between n-octanol and water (Isken & de Bont, 1996;Inoue & Horikoshi, 1989). Organic solvents with a low log P ow value show higher toxicity to micro-organisms.…”
Section: Methodsmentioning
confidence: 99%
“…Microbial resistance to solvents is based mainly on the efflux of cellular solvent influxing from the medium. In Escherichia coli, the solvent efflux is mediated by a solvent-extruding pump system (White et al, 1997;Aono et al, 1998;Tsukagoshi & Aono, 2000); similar systems are also used by Pseudomonas aeruginosa (Li et al, 1998) and Pseudomonas putida (Isken & de Bont, 1996;Kieboom et al, 1998;Ramos et al, 1998;Mosqueda & Ramos, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, resistance to antibiotics and solvents such as ethanol was found to increase in S12 with exposure to toluene but not antibiotics (279). In [ 14 C]toluene influx studies, an energydependent efflux system was proposed, as less influx was observed in adapted cells, while greater influx was observed in the presence of potassium cyanide, a respiratory chain inhibitor, and m-chlorophenylhydrazone, a proton conductor (276). The interruption of toluene metabolism through mutation of the tod genes did not affect toluene tolerance in DOT-T1E, suggesting that some other mechanism of tolerance was involved (440).…”
Section: Recently Story Et Al (587) Identified a Gene (Pbhd) Inmentioning
confidence: 99%